FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Kosyi Hadi Prayogo; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to analyze the effect of board compensation, financial sophistication for audit committee, independence board of commisioner, majority shareholding, public shareholding, and board shareholding to tax avoidance measured by effective tax rate. The study population was 416 manufacturing companies that listed in Indonesia Stock Exchange during 2012-2014. The sample used were selected by purposive sampling method. After eliminating data with  several criteria, 110 companies are identified as samples during observation period  2012-2014. Hypothesis testing is performed by using the Regression Analysis. The result of this study showed that financial sophistication for audit committee and majority shareholding structure are consistent with hypothesis which has positively significant effect on tax avoidance. In the other hand, board compensation, independence board of commisioner, public shareholding structure, and board shareholding structure are not consistent with hypothesis that has not significantly effect on tax avoidance.